Numerical modeling of the magnetization of a permanent magnet and its effect on the electromechanical performance of a brushless direct current motor - Jang, GH; Chang, JH; Lee, YB (AMER INST PHYSICS, 2002)
This article investigates the electromechanical performance of a brushless dc (BLDC) motor due to the magnetization patterns of a permanent magnet, i.e., rectangular, trapezoidal, and sinusoidal magnetization. A driving circuit equation considering the switching action of the pulse width modulation inverter is coupled with Maxwell's equation to obtain the nonlinear time-stepping finite element equation for the magnetic field analysis. Newton-Euler's equations are used to determine the mechanical motion of a rotor due to electromechanical excitation. The results show that rectangular magnetization results in the low phase current for a specified torque. However, sinusoidal magnetization produces the smallest magnetic force and may result in the sound mechanical operation of a BLDC motor. (C) 2002 American Institute of Physics.
Keywords: TORQUE